A comunicação organizacional no âmbito da metodologia 360º/ Feedback 360º - Mourão, Rita Andreia Monteiro; ISCTE – Instituto Universitário de Lisboa (2016)
The organizational communication hasbeen relevant in organizations, especially because theglobalization and the competitiveness imply a morepermanent contact between employees (Miller, 2011).However, when applied incorrectly (i.e, communicationfailures) this methodology may involve the sharingof negative feelings among employees (Proctor &Doukakis, 2003). These communication failures tendto occur in organizations with a strong hierarchicalstructure, due to the lower power sharing amongdifferent organizational actors (e.g. some organizationalactors tend to avoid their communication with othersthat have a higher hierarchical position) (Felts, 1992).Thus, seems important to conduct studies aboutorganizational communication, in the context of aspecific methodology of evaluating performance called360º methodology/360 º feedback. This methodologydiffers from the traditional performance evaluationby considering the evaluative perspective of variousorganizational actors (e.g. Brutus & Gorriti, 2005).This article aims to approach the themes of methodology360º and organizational communication, through to aliterature review about these issues.